The Evaluation of Medical Records of Gingival Recession in Chronic Periodontitis Patient - Astuti, Luki; Shafina, Syifa (Dentistry Faculty, 2023)
Background: Periodontitis is inflammation of the gingiva accompanied by alveolar bone loss, which causes loss of attachment. Local factors that can exacerbate periodontitis are gingival recession, a condition where the gingival margin is pulled away from the cemento-enamel junction (CEJ), resulting in the opening of the root surface that was initially closed. Objective: This study aimed to determine the distribution of gingival recession features in chronic periodontitis patients at the Universitas Trisakti Dental Hospital, Indonesia. Material and Methods: This type of research is an observational descriptive with a cross-sectional research design with periodic medical record samples from January 2013 to December 2017. Data obtained from medical records were recorded and grouped in tables and then analyzed manually. Results: Of the 583 periodontal patients, there were 311 patients with gingival recession consisting of 11 maxillary gingival recession patients, 21 mandibular gingival recession patients with the majority of mild classification of gingival recession (3.0 mm from the exposed root surface) and 279 patients suffering from in both jaws with the majority classification of severe gingival recession ( 4.0 mm exposed root surface). Conclusion: Gingival recession in patients with chronic periodontitis is more common in the mandible than the maxilla. Patients with chronic periodontitis mostly experience gingival recession of more than 1 tooth in the upper and lower jaw with severe classification ( 4 mm).